(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research is composed of two parts: The first is theoretical and separates the saying from the subjectification idiom with its considerable presence in criticism surrounding the immigration space. It also explains the marks and impressions which make difference between it and the factual and artistic space. The second one is applicable. It takes to pieces the image of Cairo Al Muiz in the journey of Al Abdari, considered as subjectified image and also observes its subjectification move and the effective elements in it. Its most significant result is that the immigration space has its own distinguished character as a subjectified space that lies in moderate position between the factual and artistic space, and expresses the age of journey, its culture, situations, emotions and also effect of space and period in it. Cairo in Al Abdari text which has lost both its historical sacred distance and has changed into a dismissing frightening space that it explained Al Abdari age, its believing ideal and national enthusiasm, its desolation and estrangement of the civilian form and its intimate tie to the space of the ego=mother space=his village Haha.